2007
DOI: 10.3892/or.17.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of PDCD4 expression in human glioma: Possible role in the tumorigenesis of glioma

Abstract: Abstract. Programmed cell death 4 (PDCD4) was recently identified as a novel tumor suppressor gene. The loss of PDCD4 expression was found in several types of human cancer cell lines. To date, however, the status of PDCD4 expression in human glioma tissue is not known. In the present study, the expression of PDCD4 in 30 glioma samples was determined at both mRNA and protein levels by means of RT-PCR, Western blotting, and immunohistochemistry. Herein, we demonstrate, for the first time, that 47% (14/30) of gli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
85
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 21 publications
(27 reference statements)
4
85
0
Order By: Relevance
“…The expression of the gene is modulated by many factors, including interleukins (9), retinoid (10), 12-O-tetradecanoylphorbol 13 acetate (TPA) (11,12), transforming growth factor (TGF)-β1 (13), growth factors (14,15), topoisomerase inhibitors (5) and the transcription factor myb (6,7), and is up-regulated in association with apoptosis (4,13). PDCD4 expression has been shown to be suppressed in many tumor tissues, such as lung cancers (16), pancreatic cancers (17), hepatocellular carcinomas (13), colon cancers (18), skin carcinomas (15), breast cancers (19) and glioma tissues (20). The PDCD4 protein levels are often not correlated with the mRNA levels in certain tumor tissues (16,20), indicating that PDCD4 expression is controlled at both the transcription and post-transcription levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of the gene is modulated by many factors, including interleukins (9), retinoid (10), 12-O-tetradecanoylphorbol 13 acetate (TPA) (11,12), transforming growth factor (TGF)-β1 (13), growth factors (14,15), topoisomerase inhibitors (5) and the transcription factor myb (6,7), and is up-regulated in association with apoptosis (4,13). PDCD4 expression has been shown to be suppressed in many tumor tissues, such as lung cancers (16), pancreatic cancers (17), hepatocellular carcinomas (13), colon cancers (18), skin carcinomas (15), breast cancers (19) and glioma tissues (20). The PDCD4 protein levels are often not correlated with the mRNA levels in certain tumor tissues (16,20), indicating that PDCD4 expression is controlled at both the transcription and post-transcription levels.…”
Section: Introductionmentioning
confidence: 99%
“…PDCD4 expression has been shown to be suppressed in many tumor tissues, such as lung cancers (16), pancreatic cancers (17), hepatocellular carcinomas (13), colon cancers (18), skin carcinomas (15), breast cancers (19) and glioma tissues (20). The PDCD4 protein levels are often not correlated with the mRNA levels in certain tumor tissues (16,20), indicating that PDCD4 expression is controlled at both the transcription and post-transcription levels. Recently, it was reported that microRNA-21 targets PDCD4/Pdcd4 mRNA, thereby regulating PDCD4 expression (reviewed in refs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate PDCD4 has tumor suppressor activity. Loss of PDCD4 expression has been found in several types of human cancer cell lines [14], primary lung cancer [15], primary pancreatic cancer [16], hepatocarcinoma [17], colon carcinoma [18], and gliomas [19]. Recently, Wen et al [20] reported that compared to normal breast epithelial cells, PDCD4 expression is only slightly decreased in ductal carcinoma in situ samples, but is markedly decreased in invasive ductal carcinoma samples.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of PDCD4 expression is closely associated with the progression of a number of tumors, including glioblastomas (7), and kidney, ovarian and lung cancer (8)(9)(10). Low PDCD4 expression levels correlate with poor outcomes in patients with glioblastoma multiforme (11).…”
Section: Introductionmentioning
confidence: 99%